Dynamic Economic Analysis of Marine Pollution Prevention Technologies: An Application to Double Hulls and Electronic Charts - Jin, Di; Kite-Powell, Hauke L.; Broadus, James M. (The International Hydrographic Review, 2015)
Marine pollution associated with shipping accidents has resulted in a Congressional mandate for double hulls on tankers in U.S. waters. In this paper, we formulate a social planner's problem using optimal control theory to examine the relative cost-effectiveness of double hulls and alternative pollution retention technologies, and the optimal installation strategy for such technologies. The model encompasses the costs and benefits associated with shipping operations, damage to the marine environment, and investment in each technology. A computer simulation of the model is used to evaluate investment strategies for two technological options: double hulls and electronic chart systems. Results indicate that electronic charts may be a far more cost-effective approach to marine pollution control.